Visual health and social perception of jugglers in the city of Bogotá, Colombia - Rincón-Suárez, Kelly Nataly; Jimenez-Barbosa, Ingrid Astrid (Universidad y Salud, 2017)
Introduction: Juggling is an artistic practice that includes various historical, social, cultural and economic dynamics, and nowadays it conceives new approaches regarding the artist's health. Objective: To understand the state of visual health and the social perception of juggling in the city of Bogotá. Materials and methods: A mixed study combining qualitative methodology of phenomenological type a quantitative descriptive methodology in a group of 15 jugglers of the city of Bogota, who worked at the traffic lights in the localities of Teusaquillo, Suba and Engativá, through three stages: planning; field work which includes field diary, interview and visual and ocular screening tests; and advertising campaign. Results: 100% of the participants referred to eye reddening and feeling of grit that is associated with the working hours, manipulation tools and exposure to the work environment. There are normally in the perception of depth (20" of arc) and the perception of color in the totality of participants. Conclusions: Visual and ocular health is not very important for the participating jugglers; however, they have symptoms of ocular discomfort. The juggler is perceived as a social actor that contributes to the growth of the city no matter that the common people consider this practice as unhealthy. The designed social campaign managed to sensitize pedestrians and drivers.